A Natural Hybrid of Pleroma (Melastomataceae) from Serra da Bocaina, Southeastern Brazil - Meyer, Fabrício Schmitz; Yamamoto, Manuella Aparecida Cosmo Galan; Goldenberg, Renato (Phytotaxa, 2025)
We present the description of Pleroma × venosum, a natural hybrid discovered in the Pedra da Macela region, municipality of Paraty, State of Rio de Janeiro, Brazil. This hybrid shows intermediate characters between Pleroma sellowianum and Pleroma echinatum, both also common in the same area, all of them with overlapping flowering periods. Pleroma × venosum has distinct morphological traits that set it apart from each one of its putative parent species, including differences in the type of indumentum covering the plant, leaf shape and number of veins, color and the dimensions of some floral structures. The hybrid differs from P. sellowianum by its leaves with five veins, flowers grouped in inflorescences, two bracteoles surrounding the floral bud, and flowers at anthesis with lilac petals, and yellow appendages on the pedoconnective in both stamen cycles. If compared to P. echinatum, it differs by the rugose adaxial surface of its leaves, which are covered with shorter trichomes and have a rugose (non-bullate) base, as well as by its larger, sericeous hypanthium and larger petals. For the new hybrid, a complete description is provided, as well as taxonomic comments, illustrations based on dehydrated specimens, photos of live specimens, a distribution map, and an identification key for the species of the genus that occur at Pedra da Macela. According to our assessments based on IUCN criteria, P. × venosum is Critically Endangered, because its occurrence is restricted and known from only two living plants, despite several attempts to locate more plants in the field. This is the first hybrid formally described for the genus Pleroma.